Experimental Investigation of the Yaw Misalignment Effect on the Power Performance and System Loading of a Flapping‐Foil Hydrokinetic Turbine - Dong‐Geon Kim; Jihoon Kim; Sejin Jung; Jin Hwan Ko (Energy Science & Engineering)
ABSTRACT Hydrokinetic turbines (HTs) extract power by utilizing hydrodynamic forces from flow energy. The surplus load not used for power generation acts as a system load and must be considered when designing the turbine. Additionally, due to the variability of the flow direction during tidal power generation, the effect of the yaw misalignment angle on the power generation performance and system loading is an important design consideration. This study investigates the characteristics of an experimental model of an HT that uses two flapping foils, at different yaw misalignment angles through circulating water tunnel experiments. Experimental results show that with a yaw angle change of 10°, the power performance decreases by approximately 10% and the load increases by about 30% compared to an aligned configuration. Notably, the load in the flow‐perpendicular direction was significant, with periodic changes due to repetitive up‐and‐down motions. Consequently, the hydrodynamic force characteristics of the HT differ from those of conventional rotary turbines, necessitating the development of a design method that fits these characteristics for the actual installation of flapping‐foil HTs at tidal current power generation sites.